Best of Both Worlds: Lamenting Our Path to the Future. (July 2016) - Petermann, Stephan
Abstract : After a period of decline, the Alpine valley of Andermatt in Switzerland is undergoing major development as a holiday resort by an Egyptian real estate billionaire. A documentary film on the process, by a young Swiss filmmaker, highlights the ambivalent relationship between global corporatist efforts to 'rescue' struggling rural areas, and the local communities concerned.Stephan Petermann, who is researching the future of the countryside for architect Rem Koolhaas's think tank AMO, gives an account of it.